Neuropsychological Performance Is Correlated With Tau Protein Deposition and Glucose Metabolism in Patients With Alzheimer’s Disease - Qiao, Zhen; Wang, Guihong; Zhao, Xiaobin; Wang, Kai; Fan, Di; Chen, Qian; Ai, Lin (Frontiers in Aging Neuroscience, 2022)
Objective: The aim of this study is to characterize the glucose metabolism and the distribution of tau protein deposition in patients with Alzheimer’s disease, and to evaluate the relationships between the neuropsychological performance and tau protein deposition or glucose metabolism using 18F-FDG and 18F-AV1451 PET/CT. Methods: 64 AD patients with Aβ+ and 25 healthy subjects were enrolled in this study. All subjects underwent 18F-FDG and 18F-AV1451 PET/CT. Clinical data and neuropsychological scores were collected. AD patients were divided into mild, moderate and severe group according to each neuropsychological score. The standardized uptake value ratios (SUVRs) for both FDG and AV1451 PET images were calculated with the reference region of cerebellar vermis. SUVRs in the whole cerebral cortex and brain region were calculated respectively. The volume of interest (VOI) was obtained based on the automated anatomical atlas (AAL) and Brodmann regions. Students’ t test was used to compare inter-group SUVR. Partial correlation coefficient between SUVR and neuropsychological scores was computed in an inter-subject manner using age and education as covariates. Results: Mild subgroup showed reduction of glucose metabolism and aggregation of tau protein in temporal-parietal cortex. With the decline of neuropsychiatric performance, SUVR of FDG PET decreased and SUVR of tau PET increased gradually. Glucose metabolism reduction and areas of Tau protein deposition are distributed in parietal-temporal-frontal cortex successively. Both SUVRs of FDG and tau PET were correlated with MMSE, MOCA, AVLT, BNT, CDT and VFT with statistically significance (P < 0.05). SUVRs of FDG PET was correlated with ADL and HAMD with statistically significance. There was no significant correlation between SUVRs of tau PET and ADL and HAMD. Conclusion: The extension of tau protein deposition was similar but not exactly consistent with the area of glucose metabolism reduction. Both SUVR of tau and FDG PET demonstrated correlations with cognitive function in domain-specific patterns, and the results of FDG-PET were more closely correlated with neuropsychological function than tau PET.